Effect of monotherapy with darunavir/cobicistat on viral load and semen quality of HIV-1 patients. - Miguel A López-Ruz (PLoS ONE, 2018)
Many patients previously using darunavir/ritonavir (DRV/r) (800/100mg) have switched to darunavir/cobicistat (DRV/C) (800/150 mg) either as part of triple therapy (ART) or as monotherapy with DRV (mDRV). The latter approach continues to be used in some countries for patients receiving long-term treatment. However, to date, the behaviour of DRV/C in the seminal compartment has not been analysed. This study explores how the combination behaves in monotherapy, with respect to the control of viral load and seminal quality. To this end, we studied 20 patients who were treated with mDRV/C after previous treatment with mDRV/r for at least 24 weeks. A viral load control in seminal plasma similar to that published in the literature was observed after 24 weeks of treatment with mDRV/C (viral load positivity in 20% of patients). Similarly, semen quality was confirmed (70% normozoospermic) in patients treated with this formulation, as has previously been reported for ART and mDRV/r. The DRV levels measured in seminal plasma were above EC50, regardless of whether the seminal viral load was positive or negative. We conclude that this mDRV/C co-formulation behaves like mDRV/r in seminal plasma in terms of viral load control and semen quality.